Improving High School Students’ Critical Thinking and Learning Outcomes through the Contextual Teaching and Learning (CTL) Model - Dwi Ratnaningsih; Eges Triwahyuni (Jurnal Pedagogi dan Pembelajaran, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model on improving critical thinking skills and learning outcomes of 11th grade high school students. The background of this study is the low critical thinking ability and academic achievement of students due to the dominance of conventional teacher-centered learning methods. The research used a quantitative approach with a quasi-experimental nonequivalent control group design. The research sample consisted of two classes: experimental class taught with CTL model and control class taught with conventional method. The research instruments were pretest and posttest of critical thinking ability and learning outcomes, which were analyzed descriptively and inferentially through normality test, homogeneity test, and independent sample t-test. The results showed that the average posttest score of the experimental group (77.1) and N-Gain (0.51; medium category) were higher than the control group (63.7; N-Gain = 0.25; low category). Critical thinking skills also showed a significant increase in the experimental group (N-Gain between 0.25 to 0.72), while in the control group the increase was minimal and some even decreased. The t-test results showed significant differences (p < 0.05) between the two groups on both variables. The application of CTL proved effective in improving students' concept understanding and critical thinking skills by linking learning materials to real-life contexts. It is recommended that further research apply the CTL model to other subjects and combine it with digital technology to support mastery of 21st century skills.